Factors Affecting Consumer Goods Buyers’ Choice in E-Commerce Sites: Evidence from Vietnam - PHAM, CUONG HUNG (The journal of contemporary issues in business and government, 2021)
The main purpose of this study is to find the factors affecting the consumer goods buyers’ choice on e-commerce sites in Vietnam. By using the quantitative method, the paper examines the theoretical research model and tests four hypotheses. The sample was drawn from the population of e-commerce sites in Vietnam comprising about 1,000 respondents. This study used the questionnaire method to collect primary data to test the hypotheses. Data analysis of the questionnaire was done using SPSS. The results show that there is a correlation between personal preferences of consumers on colors and brands and their actual final choice on e-commerce sites in Vietnam. The most important factor affecting the consumer goods buyers’ choice on e- commerce in Vietnam is the brand of E-commerce site, following by the color and position. Among all educational groups, respondents with a Master degree pay the biggest attention to the site’s color attribute, and those with a Bachelor degree pay more attention to the brand attribute. Women pay much more attention to the location of the products on the screen than men, as do consumers with a PhD degree, over respondents with a Bachelor or Master degree, and foreigners over Vietnamese consumers.